Determinants of Customer Loyalty in Sharia Commercial Bank Financing in The Semarang Area - Putri, Alifia Tiara; Widowati, Mustika; Hasanah, Siti (IQTISHODUNA, 2024)
This study aims to analyze the significance of service quality, trust, customer engagement, and customer value on the loyalty of financing customers at Sharia Commercial Banks in the Semarang area, both simultaneously and partially. The population in this study is all customers of Sharia Commercial Banks in the Semarang area. The sampling technique uses purposive sampling of 100 respondents. The data used in this study is primary data obtained through the distribution of questionnaires. The multiple linear regression data analysis model with the analysis technique of statistical test F, determination coefficient test (R2), and t-statistic was processed using the SPSS 25.00 program. The results of the analysis show that service quality, trust, customer engagement, and customer value simultaneously have a significant effect on the loyalty of financing customers at Sharia Commercial Banks in the Semarang area. Partially, service quality and trust have a positive and insignificant effect on customer loyalty. Meanwhile, customer engagement and customer value have a positive and significant effect on the loyalty of financing customers at Sharia Commercial Banks in the Semarang area.